Versatzstücke eines Hymnus an den Sonnen- und Schöpfergott (O. Lg Ae BJF 31a, O. ANAsh.Mus. H.O. 302+342 etc. und Lied Nr. 100 des Großen Leidener Liederzyklus I 350): Eine Gegengabe - Fischer-Elfert, Hans-W. (Zeitschrift für ägyptische Sprache und Altertumskunde, 2022)
The purpose of this communication is to show that the recently published ostracon Lg Ae BJF 31a in Basle/Switzerland carries fragments of a hymn to the sun- and creator god Amun-Re instead of a prayer. A couple of parallels on other ostraca and the collection of numerical hymns on pLeiden I 350 can be adduced to justify its attribution to the hymnic genre.